2019
DOI: 10.3892/mmr.2019.10434
|View full text |Cite
|
Sign up to set email alerts
|

Construction of engineered myocardial tissues in�vitro with cardiomyocyte‑like cells and a polylactic‑co‑glycolic acid polymer

Abstract: The aim of the present study was to explore the feasibility of the construction of engineered myocardial tissues in vitro with cardiomyocyte-like cells derived from bone marrow mesenchymal stem cells (BMMScs) and a polylactic-co-glycolic acid (PlGa) polymer. The PlGa polymer was sheared into square pieces (10x10x1 mm), sterilized by co 60 irradiation, and hydrated in Dulbecco's modified eagle's medium for 1 h. BMMScs were isolated from the bone marrow of Sprague-dawley rats and the third passage cells were ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A method that will protect vitamin E and lutein from oxidation and will improve their absorption into the cell are PLGA nanoparticles.The biodistribution of this nanoparticles formed by lactic and glycolic acids with minimal toxicity have been already tested in studies conducted on laboratory animals (mice and rats) or cell cultures [33,34]. Adsorption, distribution, metabolism and excretion of the PLGA nanoparticles are determined by a number of properties such as size, charge, hydrophobicity and targeting molecules.…”
Section: Resultsmentioning
confidence: 99%
“…A method that will protect vitamin E and lutein from oxidation and will improve their absorption into the cell are PLGA nanoparticles.The biodistribution of this nanoparticles formed by lactic and glycolic acids with minimal toxicity have been already tested in studies conducted on laboratory animals (mice and rats) or cell cultures [33,34]. Adsorption, distribution, metabolism and excretion of the PLGA nanoparticles are determined by a number of properties such as size, charge, hydrophobicity and targeting molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have explored its potential for cardiac patch development, enabling the regeneration of damaged myocardium [209]. Additionally, PLGA has been incorporated into three-dimensional constructs, promoting the formation of functional cardiac tissues that mimic native heart structures [210].…”
Section: Poly(lactic-co-glycolic Acid) (Plga)mentioning
confidence: 99%
“…Polylactic acid-glycolic acid (PLGA) is biocompatible and nontoxic, with controlled degradation rate, high porosity and good mechanical properties, and is widely used in the field of tissue engineering. 66 Xing et al 67 grew murine bone marrow mesenchymal stem cells (BMMSCs) induced with 5-Aza on PLGA scaffolds and showed that the scaffold was able to promote cell adhesion and proliferation with increased expression of cardiac-specific proteins.…”
Section: Synthetic Materialsmentioning
confidence: 99%